Settlement of Minor Crimes Against Perpetrators Who Have a Family Relationship with One of the Sarak Opat Devices - Cibro, Supiandi; Surya, Achmad (Sekolah Tinggi Ilmu Hukum Muhammadiyah Takengon, 2024)
The community in Central Aceh Regency, in resolving cases in the community, is still partly through customary law institutions, where disputes that occur are resolved by sarak opat. However, in its implementation, the community is still not satisfied with the decision of the sarak opat in the settlement of the case that occurred, because the settlement of the case through the sarak opat still has a settlement of cases that have a family relationship or the occurrence of a conflict of interest with one of the sarak opat devices. The purpose of this study is to find out the process of settling minor crimes against litigants who have a family relationship with one of the apparatus. This type of research is empirical juridical, namely legal research that is initially studied as secondary data, then continued with research on primary data in the field. The data sources used in the research are literature studies and field studies. The data were analyzed qualitatively and presented descriptively. The results of the study show that the process of settling minor crimes against litigants who have a family relationship with one of the sarak opat devices is carried out simply by emphasizing the aspect of consensus deliberation to achieve peace from the disputing parties.